2012
DOI: 10.1021/jm201346g
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Design of a Potent and Selective Inhibitor of Cytochrome P450 2C19

Abstract: A series of omeprazole-based analogues was synthesized and assessed for inhibitory activity against CYP2C19. The data was used to build a CYP2C19 inhibition pharmacophore model for the series. The model was employed to design additional analogues with inhibitory potency against CYP2C19. Upon identifying inhibitors of CYP2C19, ligand-based design shifted to attenuating the rapid clearance observed for many of the inhibitors. While most analogues underwent metabolism on their aliphatic side chain, metabolite ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…As shown in Figure 4 E,F, Val113, Phe114, Ile205, Ile366, and Phe476 were important for the interactions between sauchinone and CYP2C19. It has been reported that Val113, Phe114, Ile205, Ile366, and Phe476 are crucial residues for ligand binding in CYP2C19 [ 41 , 42 ]. Sauchinone exhibited the lowest binding energy of −1.81 kcal/mol at the active site of CYP2E1, consistent with its least inhibition against human CYP2E1 ( K i = 41.70 µM).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4 E,F, Val113, Phe114, Ile205, Ile366, and Phe476 were important for the interactions between sauchinone and CYP2C19. It has been reported that Val113, Phe114, Ile205, Ile366, and Phe476 are crucial residues for ligand binding in CYP2C19 [ 41 , 42 ]. Sauchinone exhibited the lowest binding energy of −1.81 kcal/mol at the active site of CYP2E1, consistent with its least inhibition against human CYP2E1 ( K i = 41.70 µM).…”
Section: Discussionmentioning
confidence: 99%
“…The individual CYP isoforms come in different shapes, sizes, and compositions, contributing to unique substrate specificity profiles. The key structural features of a few important CYP inhibitors have been elucidated using X-ray crystallography, pharmacophore modeling, and various other in silico approaches [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In particular, the structural features of CYP3A4 inhibitors have been well studied [ 30 , 39 , 40 , 41 , 42 , 43 ]; however, data on the specific structural features of inhibitors for the other four major cytochromes are limited and warrant further investigation.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…This can provide new avenues to find novel orthosteric/allosteric chemotypes , of GPR88 by using structure-based drug design (SBDD), such as a virtual screening strategy . Fragment-based drug design (FBDD) and ligand-based drug design ,, may also each provide efficient strategies to identify more effective and selective GPR88 agonists and also antagonists with improved druglikeness by taking advantage of privileged fragments and newly identified synthetic ligands. Moreover, it is of great value for structural biologists to resolve the GPR88 structure and GPR88 receptor–ligand complexes using biophysical methods to pave the way for mechanistic studies and rational drug design.…”
Section: Conclusion and Future Directionsmentioning
confidence: 99%